2019
DOI: 10.1002/acr.23779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical State on Pain Mediated Through Emotional Health in Rheumatoid Arthritis

Abstract: Objective. Pain is one of the main symptoms of patients with rheumatoid arthritis (RA). Pain in RA is caused by specific physical changes, such as joint destruction, and is therefore used as a disease activity marker. Although pain can also be influenced by emotional factors, neither the effect of emotional health nor the indirect effect of the physical state mediated by emotional health on pain has been quantified.Methods. A total of 548 patients with RA participated. Emotional health was assessed using the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Indeed, some genetic epidemiological studies have shown significant associations between the severity of depression and polymorphisms in inflammatory cytokine genes encoding IL-1β, IL-6, TNF and CRP [ 47 , 48 ]. Psychological stress, in turn, is thought to promote the inflammatory response via several immunomodulatory pathways [ 12 , 49 , 50 ], and can also exacerbate clinical symptoms and impair medical adherence, treatment response, and physical activity [ 8 , 9 , 51 ]. In addition, a large-scale cohort study has shown that exposure to a stress-related disorder is a risk factor for subsequent autoimmune disease [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some genetic epidemiological studies have shown significant associations between the severity of depression and polymorphisms in inflammatory cytokine genes encoding IL-1β, IL-6, TNF and CRP [ 47 , 48 ]. Psychological stress, in turn, is thought to promote the inflammatory response via several immunomodulatory pathways [ 12 , 49 , 50 ], and can also exacerbate clinical symptoms and impair medical adherence, treatment response, and physical activity [ 8 , 9 , 51 ]. In addition, a large-scale cohort study has shown that exposure to a stress-related disorder is a risk factor for subsequent autoimmune disease [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some genetic epidemiological studies have shown signi cant associations between the severity of depression and polymorphisms in in ammatory cytokine genes encoding IL-1β, IL-6, TNF and CRP [38,39]. Psychological stress, in turn, is thought to promote the in ammatory response via several immunomodulatory pathways [10,40,41], and can also exacerbate clinical symptoms and impair medical adherence, treatment response, and physical activity [7,8,42]. In addition, a large-scale cohort study has shown that exposure to a stress-related disorder is a risk factor for subsequent autoimmune disease [43].…”
Section: Discussionmentioning
confidence: 99%
“…Physical state changes (e.g., age, health status, etc.) could also worsen the perception of pain [14].…”
Section: Mechanism Of Painmentioning
confidence: 99%